The consistent psycho-social development of young footballers: Implementing the 5C's as a vehicle for interdisciplinary cohesion - Steptoe, K.; King, T.; Harwood, C. (Football Psychology - From Theory to Practice, 2019)
The development of positive psycho-social processes and psychological characteristics in youth athletes has received substantial research attention over the last decade, with a greater understanding gained of the role played by key stakeholders including peers, coaches, parents, sport scientists, and education providers. For the sport psychologist working in the professional football domain, it has become imperative to embed training of psychological skills within the multi- and interdisciplinary context. In this chapter the authors reflect on their combined experiences of working within professional football academies and the implementation of the 5C`s (Commitment, Communication, Concentration, Control, Confidence) programme to promote a cohesive message of psychological support and increase engagement from all those involved in player development. The case describes how the flexibility of the 5C`s framework fostered collaboration with members of the management team to target and define the most valued behaviours and responses agreed to represent positive psychological performance in training and competition. The initial organisational level work provided an important platform from which bespoke training programmes could be designed and implemented along the development pathway with key messages supported and reinforced by the young players` support network. The case represents the utility of the 5C`s framework in aligning approaches to psycho-social skill development and in the consistent assessment, intervention, and evaluation of psychological performance.